2016
DOI: 10.1002/adma.201601151
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap Restructuring of the Layered Semiconductor Gallium Telluride in Air

Abstract: A giant bandgap reduction in layered GaTe is demonstrated. Chemisorption of oxygen to the Te-terminated surfaces produces significant restructuring of the conduction band resulting in a bandgap below 0.8 eV, compared to 1.65 eV for pristine GaTe. Localized partial recovery of the pristine gap is achieved by thermal annealing, demonstrating that reversible band engineering in layered semiconductors is accessible through their surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
76
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 39 publications
11
76
0
2
Order By: Relevance
“…Finally, we will discuss the Raman spectrum of h‐GaTe that is still controversy in previous works. Previous work found that after long time exposure in ambient environment, the Raman pattern of m‐GaTe will turn very close to Raman pattern of h‐GaTe, therefore, the main peak of ≈ 127 and 143 cm −1 are attributed to chemisorption of oxygen to Te . However, some works based on calculation and experiment insist on the two peaks belonging to intrinsic Raman peaks of h‐GaTe .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we will discuss the Raman spectrum of h‐GaTe that is still controversy in previous works. Previous work found that after long time exposure in ambient environment, the Raman pattern of m‐GaTe will turn very close to Raman pattern of h‐GaTe, therefore, the main peak of ≈ 127 and 143 cm −1 are attributed to chemisorption of oxygen to Te . However, some works based on calculation and experiment insist on the two peaks belonging to intrinsic Raman peaks of h‐GaTe .…”
Section: Resultsmentioning
confidence: 99%
“…42 We obtained a ¼ 0.80 eV and b ¼ 1.46. The calculated energy band gaps and the tting using eqn (2) are shown in Fig. 2b.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies have been planned for determining what kind of defects give rise to X sub exactly. One possibility is O 2 adsorption as it has been established by density functional theory (DFT) calculations that the GaTe‐O 2 complex can induce intermediate band states in GaTe …”
mentioning
confidence: 99%